The right of return: its application to Palestinian refugees - Eishan Jan, Mohammad Naqib (International Islamic University Malaysia, 2005)
It is an open secret that the cause of the suffering of millions of Palestinian refugees for the past 51 years is the state of Israel for it is this state that, in disregard of all the relavant norms of international law, has adopted a wrongful policy of ethnic cleansing' - a policy that is designed to replace the Palestinians with Jewish migrants from all over the world - which has made the Palestinians endure for a very long period of time the injustices of forcible displacement from their homes that has no precedent in modern history. Israel, by making the Palestinians refugees and by inviting the Jews from all over the world to settle in the native Arab lands, has committed an internationally wrongful conduct for which she is responsible under international law. The international community, incliding the United Nations, must enforce the law in this regard by taking certain measures that aimed at not only stopping Israel from further carrying out her internationally wrongful conducts but also compelling her to rectify the wrong that she has already committed. The best way to rectify the wrong she has committed, as explained in this paper, is to restore the status quo which the Palestinians were in before the wrong was perpetrated. Restitution is possible only if the right to return of the refugees is implemented and the state of Israel is under an international obligation to allow the voluntary return of the refugees. The right of voluntary return to ones own home in his homeland is based in law. In the case od Palestinian refugees, this right not only has its basis in law, but also in justice, in equity, in history and in their ancestral tie with their homeland. Thus, the international community in general and Israel in particular, have a duty to ensure the safe and voluntary return of the Palestinian refugees to their former homes and for those who wish not to return, approriate and adequate compensation must be paid to them.